Catalyst for preparing methyl acrylate through condensation of methyl acetate and formaldehyde, preparation method of catalyst and preparation method of methyl acrylate
By using a catalyst containing zirconium-modified silica support and active components, combined with the technology of a depolymerization reactor, the problems of low yield of methyl acrylate and low catalyst selectivity are solved, and an efficient and environmentally friendly methyl acrylate production process is achieved.
Patent Information
- Application Number
- CN202311297870.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-09
AI Technical Summary
In the prior art, the yield of methyl acrylate is low and the catalyst selectivity is not high, resulting in problems such as pollution and high energy consumption in the production process.
The catalyst prepared by zirconium-containing modified silica support and active components is used to prepare the catalyst by sol-gel method, and the depolymerization of the formaldehyde source is controlled in the depolymerization reactor to realize the two-stage condensation reaction of methyl acetate and formaldehyde.
The product yield of methyl acrylate is significantly improved, and the selectivity of the catalyst is improved, and the efficiency and environmental protection of the production process are improved.
Smart Images

Figure BDA0004483585000000101 
Figure BDA0004483585000000102
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde, a preparation method thereof and a preparation method of methyl acrylate. Background Art
[0002] Methyl acrylate is an important fine chemical raw material with a wide range of uses. Currently, its preparation methods mainly include propylene oxidation method, acrylonitrile hydrolysis method, ethylene ketone method, propane oxidation method and methyl formate method, but these methods have the disadvantages of serious pollution, high energy consumption and low product yield.
[0003] CN101575290A discloses a method for synthesizing methyl acrylate by means of a catalyst segmented filling method, wherein a phosphorus-vanadium catalyst and a Cs-Sb2O5 / SiO2 catalyst are segmentedly filled to integrate two reactions to catalyze and synthesize methyl acrylate. The steps are as follows: (1) phosphoric acid is added to a vanadium lactate solution to prepare an impregnation solution having a phosphorus-vanadium molar ratio of 2.0:1-3.5:1, and the solution is impregnated onto a chromatography silica gel, and the phosphorus-vanadium catalyst is obtained by drying and calcining; (2) the obtained silica sol and Sb2O5 sol are mixed and vigorously stirred for 1-2 hours, the pH value is adjusted to 8-10 to obtain a mixed sol, a 10% ammonium nitrate solution is added to dissolve the sol, and the temperature is raised to allow the sol to return to the original state; flow, react for 6-8 hours; take out, dry and calcine to obtain a white mixed gel, grind the mixed gel into 20-40 mesh, impregnate CsNO3 with a mass content of 5%-30%, and calcine at 400-600°C for 3 hours to obtain Cs-Sb2O5 / SiO2 catalyst; (3) synthesize methyl acrylate in a fixed bed micro-reaction chromatography device, divide the reaction tube into 9 sections, and fill the phosphorus vanadium and Cs-Sb2O5 / SiO2 catalysts from top to bottom in sequence, with the phosphorus vanadium catalyst in the 2nd to 6th sections and the cesium alkali metal catalyst in the 2nd to 9th sections. Mix methyl acetate and methylal and inject them with a micro pump, the molar ratio of methyl acetate to methylal is 1:1-3:1, and the feed space velocity is 1-5h -1 , the furnace temperature is set to 350-420°C for the synthesis reaction to obtain methyl acrylate. Although it solves the problem of low reaction conversion rate, it requires additional equipment and its selectivity is not high.
[0004] Therefore, it is of great significance to develop new green and efficient production processes. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of low methyl acrylate yield in the prior art, and to provide a catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde and a preparation method thereof. The catalyst is applied to catalyze the condensation of methyl acetate and formaldehyde to prepare methyl acrylate and has high catalytic activity.
[0006] In order to achieve the above-mentioned object, the present invention provides a catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde, wherein the catalyst comprises a zirconium-modified silica carrier and an active component; the active component comprises an alkaline active center and an acidic active center.
[0007] The second aspect of the present invention provides a method for preparing the catalyst of the present invention, which comprises: S1. preparing a zirconium-modified silica carrier by a sol-gel method; S2. bringing an acidic active center source into first contact with the zirconium-modified silica carrier, first drying, calcining, bringing the acidic active center source into second contact with the alkaline active center source in a solvent, and second drying.
[0008] A third aspect of the present invention provides a method for preparing methyl acrylate by condensing methyl acetate and formaldehyde, the method comprising: contacting a formaldehyde source, methanol, methyl acetate and a catalyst for reaction; the catalyst comprises the catalyst described in the present invention.
[0009] Through the above technical solution, the present invention has the following beneficial effects:
[0010] The invention provides a catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde, comprising a zirconium-modified silica carrier and an active component; the active component comprises an alkaline active center and an acidic active center; and the catalyst is applied to a method for preparing methyl acrylate by condensing methyl acetate and formaldehyde. By controlling the supply amount of formaldehyde monomer provided by a formaldehyde source and the ratio of methyl acetate to methanol, a depolymerization reactor is used to depolymerize the formaldehyde source into monomer formaldehyde, so that methyl acetate and formaldehyde can be catalyzed to carry out a two-stage condensation reaction at the same time, thereby effectively improving the product yield of methyl acrylate. DETAILED DESCRIPTION
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0012] The invention provides a catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde. The catalyst comprises a zirconium-modified silicon dioxide carrier and an active component; the active component comprises an alkaline active center and an acidic active center.
[0013] The catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde has the advantage of catalyzing methyl acetate and formaldehyde simultaneously. The catalyst is conducive to obtaining a higher yield of methyl acrylate product.
[0014] According to a particularly preferred embodiment of the present invention, based on the total mass of the catalyst, the content of the active component is 1-25wt%, preferably 5-20wt%. By adopting the above preferred embodiment, the yield of methyl acrylate can be further improved.
[0015] In the present invention, there is no special requirement for the mass content ratio of the basic active center to the acidic active center. According to a particularly preferred embodiment of the present invention, based on 100wt%, the mass content ratio of the basic active center to the acidic active center is 1-150, preferably 5-100. In the embodiments, 5, 10.6, and 100 are used as exemplary illustrations, but the scope of the present invention is not limited thereto. By adopting the aforementioned preferred embodiment, the catalytic activity can be further improved.
[0016] In the present invention, there is no special requirement for the provision of the basic active center, which is exemplary, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the basic active center is provided by a potassium compound. By adopting the aforementioned preferred embodiment, the catalytic activity can be further improved.
[0017] In the present invention, there is no special requirement for the provision of the acidic active center, which is exemplary, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the acidic active center is provided by a phosphorus compound and / or a boron compound, and preferably the acidic active center exists in the form of phosphorus oxide and / or boron oxide. By adopting the above preferred embodiment, the catalytic activity can be further improved.
[0018] In the present invention, there is no special requirement for the content of the zirconium-modified silica carrier, which is exemplary, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the zirconium content is 0.5-10% by weight, preferably 1-5% by weight, based on the total mass of the zirconium-modified silica carrier. By adopting the above preferred embodiment, the catalytic activity can be further improved.
[0019] According to a preferred embodiment of the present invention, based on the total mass of the catalyst, the content of the potassium compound is 1-30% by weight, preferably 5-25% by weight, more preferably 5-20% by weight. In the embodiments, 5% by weight, 10% by weight and 18% by weight are exemplified, but the scope of the present invention is not limited thereto.
[0020] According to a preferred embodiment of the present invention, based on the total mass of the catalyst, the content of phosphorus oxide and / or boron oxide is 0.01-3% by weight, preferably 0.1-2% by weight, and 0.1% by weight, 1% by weight and 1.7% by weight are used as examples in the embodiments, but the scope of the present invention is not limited thereto.
[0021] By adopting the above-mentioned preferred embodiment, the catalytic activity can be further improved.
[0022] The catalyst for preparing methyl acrylate by condensation of methyl acetate and formaldehyde having the above-mentioned characteristics can be used in the present invention, and there is no special requirement for its preparation method. According to the present invention, a preparation method of the catalyst for preparing methyl acrylate by condensation of methyl acetate and formaldehyde is provided, and the method comprises: S1. preparing a zirconium-modified silica carrier by a sol-gel method; S2. bringing an acidic active center source into first contact with the zirconium-modified silica carrier, first drying, and after calcination, bringing it into second contact with an alkaline active center source in a solvent, and second drying.
[0023] In the present invention, the zirconium-modified silica carrier is prepared by a sol-gel method in step S1, and the preparation method comprises mixing a silicon source and a zirconium precursor in a solution, adjusting the pH, reacting under crystallization conditions, filtering, washing, drying and calcining.
[0024] This is an exemplary description, but does not limit the scope of the present invention. According to one embodiment of the present invention, in the present invention, the silicon source and the zirconium precursor in step S1 need to be first mixed evenly in a solution, and the solution can be deionized water. There is no special requirement for the amount, which is well known to those skilled in the art and can be selected according to actual operations.
[0025] This is for exemplary purposes only and does not limit the scope of the present invention. According to one embodiment of the present invention, in the present invention, the silicon source in step S1 uses 40 wt % alkaline silica sol as an exemplary description, but this does not limit the scope of the present invention.
[0026] In the present invention, in step S1, there is no special requirement for the mixing conditions of the silicon source and the zirconium precursor in the solution. For exemplary explanation, the mixing is immersion contact mixing, but the scope of the present invention is not limited thereto.
[0027] In the embodiment of the present invention, the solution selected for adjusting the pH in step S1 is 35 wt % nitric acid for exemplary purposes, but does not limit the scope of the present invention.
[0028] In the present invention, the pH value in step S1 has a wide range of optional values. According to a preferred embodiment of the present invention, the adjusted pH value is 0-7, preferably 1-5. In the embodiment, pH 4 is used as an exemplary description, but the scope of the present invention is not limited thereto. By adopting the aforementioned preferred embodiment, the catalytic activity can be further improved.
[0029] In the present invention, there is no special requirement for the crystallization conditions in step S1. According to a preferred embodiment of the present invention, the crystallization conditions include: a temperature of 10-100°C, preferably 75-90°C. In the embodiment, 80°C is used as an exemplary illustration, but the scope of the present invention is not limited thereby.
[0030] In the present invention, the crystallization time is adjusted as needed, which is exemplary, but does not limit the scope of the present invention. For example, the crystallization time is 1-30 hours, preferably 5-6 hours. In the embodiment, 6 hours is used as an exemplary description, but does not limit the scope of the present invention. By adopting the above preferred embodiments, the catalytic activity can be further improved.
[0031] In the present invention, there is no special requirement for the drying conditions in step S1.
[0032] According to a preferred embodiment of the present invention, the drying temperature is 10-200° C., preferably 100-110° C., and 100° C. is used as an exemplary description in the examples, but the scope of the present invention is not limited thereby.
[0033] According to a preferred embodiment of the present invention, the drying time is 1-20 hours. In the embodiment, 6 hours is used as an exemplary illustration, but the scope of the present invention is not limited thereby.
[0034] By adopting the above-mentioned preferred embodiment, the catalytic activity can be further improved.
[0035] In the present invention, there is no special requirement for the calcination conditions in step S1. According to a preferred embodiment of the present invention, the calcination temperature is 300-1000°C, preferably 800-900°C. In the embodiment, 800°C is used as an exemplary illustration, but the scope of the present invention is not limited thereby.
[0036] In the present invention, the calcination time in step S1 is adjusted as needed, generally 1-25 hours. In the embodiment, 4 hours is used as an exemplary illustration, but the scope of the present invention is not limited thereto.
[0037] In the present invention, the solvent used for washing is deionized water, and there are no special requirements for the number of washing times and the amount of deionized water used, which only need to meet the actual experimental requirements.
[0038] In the present invention, in step S2, there are no special requirements for the first drying and second drying conditions.
[0039] This is for illustrative purposes only and does not limit the scope of the present invention. According to one embodiment of the present invention, the first drying and second drying temperatures are each 10-200°C, preferably 110-120°C. In the examples, 110°C is used as an illustrative purpose only and does not limit the scope of the present invention.
[0040] According to an embodiment of the present invention, the time of the first drying and the second drying is adjusted as needed, generally 1-20 hours. In the embodiment, 6 hours is used as an exemplary illustration, but the scope of the present invention is not limited thereto.
[0041] In the present invention, the second drying of the present invention is carried out in a reactor, which is well known to those skilled in the art and can be carried out with reference to the prior art, and the invention will not be described in detail here.
[0042] By adopting the above-mentioned preferred embodiment, the dispersion of active centers can be further improved.
[0043] In the present invention, in step S2, the calcination conditions can be selected with reference to the prior art.
[0044] According to a preferred embodiment of the present invention, the calcination temperature is 100-1000°C, preferably 400-800°C.
[0045] According to a preferred embodiment of the present invention, the calcination time is 1-16 hours.
[0046] In the present invention, in step S2, the first contact condition has no special requirements and is described by way of example as immersion contact mixing, but the scope of the present invention is not limited thereby.
[0047] In the present invention, in step S2, there is no special requirement for the second contact condition. For exemplary explanation, the contact is immersion contact, but the scope of the present invention is not limited thereby.
[0048] For exemplary explanation, but not limiting the scope of the present invention, according to a preferred embodiment of the present invention, after the second contact, the second pre-drying condition includes: using at least one of toluene, xylene and trimethylbenzene as solvent, azeotropically dehydrating the solid obtained by contact; preferably, the dehydration temperature is 80-110°C, and the dehydration time is 3-8h. In the embodiment, the dehydration temperature is 100°C and the dehydration time is 5h as an exemplary explanation, but not limiting the scope of the present invention. By adopting the above preferred embodiment, the effect of active center dispersion can be further improved.
[0049] In the present invention, in the second contacting step, after the catalyst is subjected to azeotropic dehydration and before the second drying, the catalyst covered with an organic solvent on the surface needs to be loaded into the reactor, and a nitrogen purge step is performed during the reaction. This operation step is well known to those skilled in the art and can be performed with reference to the prior art.
[0050] The invention provides a method for preparing methyl acrylate by condensing methyl acetate and formaldehyde. The method comprises: contacting a formaldehyde source, methanol, methyl acetate and a catalyst for reaction; the catalyst comprises the catalyst for preparing methyl acrylate by condensing methyl acetate and formaldehyde according to the invention.
[0051] In the present invention, the formaldehyde source can be a conventional choice in the art. According to a preferred embodiment of the present invention, the formaldehyde source is at least one of methylal, trioxymethylene, polyformaldehyde and water formaldehyde, preferably polyformaldehyde, more preferably polyformaldehyde is depolymerized in a depolymerization reactor to form monomeric formaldehyde. By adopting the aforementioned preferred embodiment, the contact between methyl acetate and monomeric formaldehyde can be further improved.
[0052] In the present invention, the depolymerization conditions can be carried out with reference to the prior art.
[0053] According to a preferred embodiment of the present invention, the depolymerization temperature is 80-250° C., preferably 100-230° C., and 180° C. is used as an example in the examples, but the scope of the present invention is not limited thereto.
[0054] According to a preferred embodiment of the present invention, the depolymerization time is 1-60 s, preferably 2-35 s. In the examples, 10 s is used as an example, but the scope of the present invention is not limited thereto.
[0055] By adopting the above-mentioned preferred embodiment, the yield of methyl acrylate can be further improved.
[0056] In the present invention, there is no special requirement for the conditions of the contact reaction.
[0057] For illustrative purposes only but not to limit the scope of the present invention, according to a preferred embodiment of the present invention, the contact reaction is carried out in the presence of an inert gas.
[0058] According to a preferred embodiment of the present invention, the contact reaction preferably includes a first contact and a second contact; the first contact and the second contact reactions are respectively carried out in a first reactor and a second reactor; after the reaction raw materials are fed into the first reactor for reaction, the reaction stream after the first contact is fed into the second reactor and a formaldehyde source methanol solution is introduced; the inert gas flow rate of each of the first contact and the second contact can be selected in a wide range, and those skilled in the art can adjust according to actual needs, for example, the inert gas flow rate of the first contact is 20-400 mL / min, and the inert gas flow rate of the second contact is 50-650 mL / min. It is exemplified in the embodiments that the inert gas flow rate in the first contact is 90 ml / min of nitrogen, and the inert gas flow rate in the second contact is 160 ml / min of nitrogen, but the scope of the present invention is not limited thereby.
[0059] This is an exemplary description, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the reaction raw materials include methyl acetate, formaldehyde and methanol, and the molar ratio of methyl acetate to the formaldehyde source is (1-15):1, preferably (3-12):1, based on the total weight of the liquid raw material, and the methanol content is 1-40wt%, preferably 10-35wt%.
[0060] In the present invention, the conditions for the first contact and the second contact can be selected in a wide range, which is exemplified below, but the scope of the present invention is not limited thereby.
[0061] This is for exemplary purposes only and does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the reaction raw materials include methyl acetate, formaldehyde and methanol. The molar ratio of methyl acetate to the formaldehyde source in the first contacting step is (5-15):1, preferably (7-12):1, based on formaldehyde. The methanol content is 1-40wt%, preferably 10-35wt%, based on the total weight of the liquid raw material.
[0062] This is for illustrative purposes only and does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the present invention, the formaldehyde source methanol solution introduced in the second contacting step; and the methanol content is 0.1-40wt%, preferably 5-32wt%, calculated as formaldehyde. In the embodiment, the mass content of paraformaldehyde calculated as formaldehyde is 30wt% as an exemplary description, but this does not limit the scope of the present invention.
[0063] According to a preferred embodiment of the present invention, the temperatures of the first contact and the second contact are respectively 280-400° C., and 320° C. is used as an example in the embodiments, but the scope of the present invention is not limited thereto.
[0064] According to a preferred embodiment of the present invention, the pressures of the first contact and the second contact are respectively 0.1-0.8 MPa. In the embodiment, 0.2 MPa is used as an example, but the scope of the present invention is not limited thereto.
[0065] According to a preferred embodiment of the present invention, the liquid phase volume flow rate of the first contact is 0.01-0.2 mL / min. In the examples, the liquid phase volume flow rate of the first contact is 0.1 ml / min as an exemplary illustration, but the scope of the present invention is not limited thereto.
[0066] According to a preferred embodiment of the present invention, the liquid phase volume flow rate of the second contact is 0.005-0.1 mL / min. In the examples, the liquid phase volume flow rate of the second contact is 0.03 ml / min as an exemplary illustration, but the scope of the present invention is not limited thereto.
[0067] According to a preferred embodiment of the present invention, the gas space velocity Q1 of the first contact reaction is 2 min-1 -20min -1 , preferably 4min -1 -6min -1 In the embodiment, 5min -1 This is intended to be an illustrative example, but does not limit the scope of the invention.
[0068] According to a preferred embodiment of the present invention, the second contact gas space velocity Q1 is 5min -1 -16min -1 , preferably 8min -1 -10min -1 .
[0069] According to a preferred embodiment of the present invention, the first contacting gas space velocity Q1 is lower than the second contacting gas space velocity Q2.
[0070] By adopting the above-mentioned preferred embodiment, the yield of methyl acrylate can be further improved.
[0071] In the following examples, the conversion rate of methyl acetate and the selectivity of methyl acrylate are well known to those skilled in the art and can be carried out with reference to the prior art, and the present invention will not be elaborated herein;
[0072] In the following examples, the inert gas flow rate in the first contact in the first reactor is 90 ml / min of nitrogen, and the inert gas flow rate in the second contact in the second reactor is 160 ml / min of nitrogen.
[0073]
[0074]
[0075] Example 1
[0076] (1) A zirconium-modified silica carrier was prepared by a sol-gel method, with 40 wt% alkaline silica sol as a silicon source, zirconium oxychloride as a zirconium precursor, and a target loading amount of zirconium element on the carrier of 3 wt%. The pH was adjusted to 4 by 35 wt% nitric acid, and crystallized at 80° C. for 6 h. The carrier was filtered, washed with deionized water for 3 times, dried at 100° C. for 6 h, and calcined at 800° C. for 4 h to obtain a zirconium-modified silica carrier.
[0077] (2) Then, the ammonium phosphate solution is impregnated on the aforementioned carrier by an impregnation method, dried at 100°C for 7h, and calcined at 500°C for 4h, with a P oxide loading content of 0.1% by weight. Then, a potassium carbonate solution is impregnated by an impregnation method to obtain a solid, with a potassium carbonate loading of 10% by weight. The loaded solid is azeotropically dehydrated with toluene as a solvent, the dehydration temperature is 100°C, and the dehydration is performed for 5h. Then, the catalyst with an organic solvent covering the surface is loaded into a reactor, purged with nitrogen during the reaction, and dried at 110°C for 6h;
[0078] (3) performing a first contact and a second contact in two reactors (inner diameter 16 mm, length 1500 mm) connected in series, respectively; wherein the polyformaldehyde is first depolymerized in a depolymerization reactor to obtain formaldehyde, the depolymerization temperature is 180° C., and the depolymerization residence time is 10 s;
[0079] The first reactor and the second reactor are both filled with 10 g of the above catalyst;
[0080] First reactor: temperature 320℃, pressure 0.2MPa, space velocity 5min -1 The reaction was carried out, the feed rate (liquid phase volume flow rate) of the reaction raw materials (methyl acetate, formaldehyde, methanol) was 0.1 ml / min, the molar ratio of methyl acetate to formaldehyde in the reaction raw materials was 7:1, and the methanol content was 12 wt%;
[0081] Second reactor: temperature 320℃, pressure 0.2MPa, space velocity 10min -1 After the reaction in the first reactor is completed, the reaction materials enter the second reactor, and methanol formaldehyde solution is introduced at the same time. The formaldehyde content is 30wt%, the feed amount (liquid phase volume flow rate) is 0.03ml / min, the methyl acetate conversion rate is 23%, the methyl acrylate selectivity is 90%, and the catalyst runs stably for 350h.
[0082] Example 2
[0083] (1) A zirconium-modified silica carrier was prepared by a sol-gel method, with 40 wt% alkaline silica sol as a silicon source, zirconium oxychloride as a zirconium precursor, and a target loading amount of zirconium element on the carrier of 1 wt%. The pH was adjusted to 4 by 35 wt% nitric acid, and crystallized at 80° C. for 6 h. The carrier was filtered, washed with deionized water for 3 times, dried at 100° C. for 6 h, and calcined at 800° C. for 4 h to obtain a zirconium-modified silica carrier.
[0084] (2) Then, the ammonium phosphate solution is impregnated on the aforementioned carrier by an impregnation method, dried at 100°C for 7h, and calcined at 400°C for 6h, and the P oxide loading content is 1% by weight. Then, the potassium carbonate solution is impregnated by an impregnation method to obtain a solid, and the potassium carbonate loading is 5% by weight. The loaded solid is azeotropically dehydrated with toluene as a solvent, and the dehydration temperature is 100°C for 5h. Then, the catalyst with the surface covered with an organic solvent is loaded into a reactor, purged with nitrogen during the reaction, and dried at 110°C for 6h;
[0085] (3) performing a first contact and a second contact in two reactors (inner diameter 16 mm, length 1500 mm) connected in series, respectively; wherein the polyformaldehyde is first depolymerized in a depolymerization reactor to obtain formaldehyde, the depolymerization temperature is 180° C., and the depolymerization residence time is 10 s;
[0086] The first reactor and the second reactor are both filled with 10 g of the above catalyst;
[0087] First reactor: temperature 320℃, pressure 0.2MPa, space velocity 5min -1 The reaction was carried out, the feed rate (liquid phase volume flow rate) of the reaction raw materials (methyl acetate, formaldehyde, methanol) was 0.1 ml / min, the molar ratio of methyl acetate to formaldehyde in the reaction raw materials was 9:1, and the methanol content was 30 wt%;
[0088] Second reactor: temperature 320℃, pressure 0.2MPa, space velocity 8min -1 After the reaction in the first reactor is completed, the reaction materials are fed into the second reactor, and a methanol formaldehyde solution is introduced at the same time, the formaldehyde content is 30wt%, the feed amount (liquid phase volume flow rate) is 0.03ml / min, and the evaluation method is the same as step (4) in Example 1. The conversion rate of methyl acetate is 22%, the selectivity is 91%, and the catalyst runs stably for 350h.
[0089] Example 3
[0090] (1) A zirconium-modified silica carrier was prepared by a sol-gel method, with 40 wt% alkaline silica sol as a silicon source, zirconium oxychloride as a zirconium precursor, and a target loading amount of zirconium element on the carrier of 5 wt%. The pH was adjusted to 4 by 35 wt% nitric acid, and crystallized at 80° C. for 6 h. The carrier was filtered, washed with deionized water for 3 times, dried at 100° C. for 6 h, and calcined at 800° C. for 4 h to obtain a zirconium-modified silica carrier.
[0091] (2) Then, the ammonium phosphate solution was impregnated on the aforementioned carrier by an impregnation method, dried at 100°C for 7h, and calcined at 750°C for 10h, and the P oxide loading content was 1.7% by weight. Then, the potassium carbonate solution was impregnated by an impregnation method to obtain a solid, and the potassium carbonate loading was 18% by weight. The loaded solid was azeotropically dehydrated with toluene as a solvent, and the dehydration temperature was 100°C for 5h. Then, the catalyst with the organic solvent covering the surface was loaded into a reactor, purged with nitrogen during the reaction, and dried at 110°C for 6h;
[0092] (3) performing a first contact and a second contact in two reactors (inner diameter 16 mm, length 1500 mm) connected in series, respectively; wherein the polyformaldehyde is first depolymerized in a depolymerization reactor to obtain formaldehyde, the depolymerization temperature is 180° C., and the depolymerization residence time is 10 s;
[0093] The first reactor and the second reactor are both filled with 10 g of the above catalyst;
[0094] First reactor: temperature 320℃, pressure 0.2MPa, space velocity 5min -1 The reaction was carried out, the feed rate (liquid phase volume flow rate) of the reaction raw materials (methyl acetate, formaldehyde, methanol) was 0.1 ml / min, the molar ratio of methyl acetate to formaldehyde in the reaction raw materials was 12:1, and the methanol content was 34 wt%;
[0095] Second reactor: temperature 320℃, pressure 0.2MPa, space velocity 8min -1 After the reaction in the first reactor is completed, the reaction materials are fed into the second reactor, and a methanol formaldehyde solution is introduced at the same time, the formaldehyde content is 30wt%, the feed amount (liquid phase volume flow rate) is 0.03ml / min, and the evaluation method is the same as step (4) in Example 1. The conversion rate of methyl acetate is 21%, the selectivity is 88%, and the catalyst runs stably for 350h.
[0096] Example 4
[0097] All conditions are the same as those in Example 1, except that in step (3): the molar ratio of methyl acetate to formaldehyde in the reaction raw materials is 13:1;
[0098] Using the same evaluation method as step (4) in Example 1, the methyl acetate conversion rate was 17%, the selectivity was 92%, and the catalyst operated stably for 350 hours.
[0099] Example 5
[0100] All conditions were the same as in Example 1, except that in step (3): the methanol content in the reaction raw material feed was 8 wt%;
[0101] The conversion rate of methyl acetate was 19%, the selectivity was 78%, and the catalyst operated stably for 150 hours.
[0102] Example 6
[0103] All conditions are the same as those in Example 1, except that in step (3): the paraformaldehyde is not depolymerized in the depolymerization reactor and is directly fed in place of formaldehyde;
[0104] The conversion rate of methyl acetate was 15%, the selectivity was 81%, and the catalyst operated stably for 150 hours.
[0105] Example 7
[0106] All conditions were the same as in Example 1, except that in step (3): the space velocity in the second reactor was 1 min -1 ;
[0107] Using the same evaluation method as step (4) in Example 1, the methyl acetate conversion rate was 14%, the selectivity was 68%, and the catalyst operated stably for 70 hours.
[0108] Example 8
[0109] All conditions are the same as those in Example 1, except that in step (2): the ammonium phosphate solution is then impregnated on the aforementioned carrier by an impregnation method (the impregnation amount is the same as in Example 1), dried at 100°C for 7 hours, and calcined at 900°C for 4 hours, and then a potassium carbonate solution is impregnated by an impregnation method to obtain a solid (the impregnation amount is the same as in Example 1). The loaded solid is azeotropically dehydrated with toluene as a solvent at a dehydration temperature of 100°C for 5 hours, and then the catalyst with an organic solvent covering its surface is loaded into a reactor, purged with nitrogen during the reaction, and dried at 110°C for 6 hours.
[0110] Using the same evaluation method as step (4) in Example 1, the methyl acetate conversion rate was 12%, the selectivity was 86%, and the catalyst operated stably for 150 hours.
[0111] Comparative Example 1
[0112] All conditions are the same as those in Example 1, except that in step (2): only the potassium carbonate solution is impregnated on the aforementioned carrier by the impregnation method (the impregnation amount is the same as in Example 1), followed by azeotropic dehydration using toluene as the solvent, the dehydration temperature is 100°C, the dehydration is carried out for 5 hours, and then the catalyst with the surface covered with the organic solvent is loaded into the reactor, nitrogen is used for purging during the reaction, and the catalyst is dried at 110°C for 6 hours.
[0113] Using the same evaluation method as step (4) in Example 1, the methyl acetate conversion rate was 10%, the selectivity was 78%, and the catalyst operated stably for 50 hours.
[0114] Methyl acetate conversion rate / % Methyl acrylate selectivity / % Catalyst stable operation / h Example 1 23 90 350 Example 2 22 91 350 Example 3 21 88 350 Example 4 17 92 350 Example 5 19 78 150 Example 6 15 81 150 Example 7 14 68 70 Example 8 12 86 150 Comparative Example 1 10 78 50
[0115] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for preparing methyl acrylate by condensation of methyl acetate and formaldehyde, characterized in that: The catalyst comprises a zirconium-modified silicon dioxide carrier and an active component; the active component comprises an alkaline active center and an acidic active center.
2. The catalyst according to claim 1, wherein Based on the total mass of the catalyst, the content of the active component is 1-25wt%, preferably 5-20wt%; and / or Based on 100 wt%, the mass ratio of the basic active center to the acidic active center is 1-150, preferably 5-100; and / or The alkaline active center is provided by a potassium compound; and / or The acidic active center is provided by a phosphorus compound and / or a boron compound, preferably the acidic active center exists in the form of a boron oxide and / or a phosphorus oxide; and / or The zirconium content is 0.5-10 wt %, preferably 1-5 wt %, based on the total mass of the carrier; Preferably, Based on the total mass of the catalyst, the potassium compound content is 1-30 wt%, preferably 5-25 wt%, more preferably 5-20 wt%; and / or The content of the phosphorus oxide and / or boron oxide is 0.01-3% by weight, preferably 0.1-2% by weight.
3. A method for preparing the catalyst according to claim 1 or 2, characterized in that: The method includes: S1. preparing zirconium-modified silica support by sol-gel method; S2. The acidic active center source is first contacted with the zirconium-modified silica carrier, first dried, calcined, and then second contacted with the alkaline active center source in a solvent, and second dried.
4. The preparation method according to claim 3, wherein In step S1, the sol-gel method preparation includes: mixing the silicon source and the zirconium precursor in a solution, adjusting the pH, and then reacting under crystallization conditions, followed by suction filtration, washing, drying, and calcining.
5. The preparation method according to claim 4, wherein: In step S1, The adjusted pH value is 0-7, preferably 1-5; and / or The crystallization conditions include: a temperature of 10-100°C, preferably 75-90°C; and / or a time of 1-30h, preferably 5-6h; and / or The drying conditions include: a temperature of 10-200°C, preferably 100-110°C; and / or a time of 1-20h; and / or The calcination conditions include: a temperature of 300-1000° C., preferably 800-900° C.; and / or a calcination time of 1-25 h.
6. The preparation method according to any one of claims 3 or 5, wherein: In step S2, The calcination conditions include: The calcination temperature is 100-1000°C, preferably 400-800°C; and / or the time is 1-16h; and / or The first drying and second drying conditions each include: The temperature is 10-200°C, preferably 110-120°C; and / or the time is 1-20h; and / or After the second contact and before the second drying, the solid obtained by the contact is azeotropically dehydrated using at least one of toluene, xylene and trimethylbenzene as a solvent; preferably, the dehydration temperature is 80-110° C. and the dehydration time is 3-8 hours.
7. A method for preparing methyl acrylate by condensing methyl acetate and formaldehyde, the method comprising: contacting a formaldehyde source, methanol, methyl acetate and a catalyst for reaction; The catalyst comprises the catalyst according to claim 1 or 2.
8. The method according to claim 7, wherein: The formaldehyde source is at least one of methylal, trioxymethylene, polyformaldehyde and water formaldehyde, preferably polyformaldehyde, more preferably polyformaldehyde is depolymerized in a depolymerization reactor to form monomeric formaldehyde.
9. The method according to claim 8, wherein: The depolymerization conditions include: The temperature is 80-250°C, preferably 100-230°C; and / or The time is 1-60s, preferably 2-35s.
10. The method according to any one of claims 7 to 9, wherein: The conditions of the contact reaction include: The contact reaction is carried out in the presence of an inert gas; Preferably, the contact reaction includes a first contact and a second contact; and / or the first contact and the second contact reaction are respectively carried out in a first reactor and a second reactor; after the reaction raw materials are fed to the first reactor for reaction, the reaction stream after the first contact is fed to the second reactor; and / or The reaction raw materials include methyl acetate, formaldehyde and methanol, the molar ratio of methyl acetate to formaldehyde source is (1-15):1, preferably (3-12):1, based on the total weight of the liquid raw materials, and the methanol content is 1-40wt%, preferably 10-35wt%; Preferably, the reaction raw materials include methyl acetate, formaldehyde and methanol, and the molar ratio of methyl acetate to formaldehyde source in the first contact is (5-15):1, preferably (7-12):1, based on the total weight of the liquid raw materials, and the methanol content is 1-40wt%, preferably 10-35wt%; the second contact introduces a methanol solution of the formaldehyde source, and the formaldehyde source content is 0.1-40wt%, preferably 5-32wt% based on formaldehyde; and / or The temperatures of the first contact and the second contact are each 280-400° C.; and / or The pressures of the first contact and the second contact are each 0.1-0.8 MPa; and / or The liquid phase volume flow rate of the first contact is 0.01-0.2 mL / min; and / or The liquid phase volume flow rate of the second contact is 0.005-0.1 mL / min; and / or The first contact gas space velocity Q1 is 2min -1 -20min -1 , preferably 4min -1 -6min -1 ; and / or The second contact gas space velocity Q2 is 5min -1 -25min -1 , preferably 8min -1 -10min -1 ; and / or The first contacting gas space velocity Q1 is lower than the second contacting gas space velocity Q2.
Citation Information
Patent Citations
Method for synthesizing methyl acrylate by means of filling catalysts in sections
CN101575290A
Catalyst for synthesizing methyl acrylate by using methyl acetate and methylal and preparation method thereof
CN102941113A
Catalyst for synthesizing acrylic acid (ester) by taking formaldehyde and acetic acid as raw materials and preparation method thereof
CN103611522A
Method for preparing methyl methacrylate catalyst through aldol condensation, catalyst and application
CN109364908A
Acid-base bifunctional catalyst for synthesis of methyl methacrylate by methyl propionate and formaldehyde
CN109999922A